2016
DOI: 10.1111/hequ.12110
|View full text |Cite
|
Sign up to set email alerts
|

Mutuality, Metaphor and Micropolitics in Collaborative Governance: a Joint Venture in UK Higher Education

Abstract: As market‐led higher education systems become the ‘new normal’, a wider variety of organisational forms is likely to emerge. This paper reports on the findings of a qualitative and historical study that aimed to explore the meaning of collaborative governance in a unique and long‐standing higher education joint venture in England. Semi‐structured interviews were conducted with senior‐level stakeholders from both participating institutions: architects of the joint venture, institutional leaders and faculty mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…For co-production studies, the implications are twofold. First, the research contributes to the study of collaboration in the context of education, showing that scholars’ efforts are important, as suggested by Henderson and Trede (2017), Eldridge et al (2018), Ross and Woodfield (2017), O’Toole and Meier (2004) and Paletta (2012). The significance of adopting a co-production approach was evident during the entire project that represents a best practice in addressing the crisis of school dropouts, in sharing and valorising stakeholder competencies, involving parents and collaborating with teachers.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For co-production studies, the implications are twofold. First, the research contributes to the study of collaboration in the context of education, showing that scholars’ efforts are important, as suggested by Henderson and Trede (2017), Eldridge et al (2018), Ross and Woodfield (2017), O’Toole and Meier (2004) and Paletta (2012). The significance of adopting a co-production approach was evident during the entire project that represents a best practice in addressing the crisis of school dropouts, in sharing and valorising stakeholder competencies, involving parents and collaborating with teachers.…”
Section: Discussionmentioning
confidence: 82%
“…An ideal approach would include a collaborative approach with multiple stakeholders for public service production and the response of failures of policy implementation and high cost of public regulation (Ansell and Gash, 2008). This approach has recently found application in education (Eldridge et al , 2018; Henderson and Trede, 2017; Ross and Woodfield, 2017; Palmér and Johansson, 2018). This has led to the improvement of social capital, shared meaning, trust among participants and public problem-solving ability (Leach and Sabatier, 2005; Rogers and Weber, 2010), from the ideating public service to production and delivery (Loeffler and Bovaird, 2016; Osborne et al , 2016; Paletta, 2012; Pestoff et al , 2006).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In higher education in England, it has been found that tensions may need to be resolved when balancing mutual interests among or between joint ventures in educational j JOURNAL OF KNOWLEDGE MANAGEMENT j organizations (Ross and Woodfield, 2017). Conceptual understanding and knowledge about collaborations may include shared metaphors, such as "marriage" between partners.…”
Section: Collaboration and Knowledge Sharingmentioning
confidence: 99%